Methods and Tools for Developing Critical Thinking of Students in Literary Education (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article talks about methods and means of teaching students to think critically in the process of literary education. Ways to develop a system of questions aimed at developing students' research skills are shown.